Evaluating strengths and opportunities for a co-created climate change curriculum: Medical student perspectives - Liu, Irene; Rabin, Benjamin; Manivannan, Madhu; Laney, Emaline; Philipsborn, Rebecca (Frontiers in Public Health, 2022)
Introduction: Medical trainees are front-line workers in our worsening climate and health crisis. A movement is underway to teach medical students essential climate change and health content. Few evaluations of climate and health curricula exist to support ongoing curricular development, innovation, and improvement. Methods: The authors introduced a novel, disseminated, and co-created pre-clinical climate change and health curriculum at Emory University School of Medicine in August of 2020 for all students in the class of 2024. Extending the co-creation approach to evaluation, the authors conducted focus groups with the inaugural cohort during their 2nd year. In this qualitative evaluation, the authors coded focus group results via an inductive content analysis approach. Results: Thirteen students participated in the focus groups which elicited student perspectives across four domains: i) prior perceptions of climate change and health, ii) current attitudes about climate change and health, iii) reflections on the existing curriculum, and iv) opportunities for the curriculum. Implementation strategies that students valued included contextualization and integration of climate content within existing topics and student representation through the co-creation process. Students recommended bolstering small group lessons and case-based learning to build history and physical exam skills as well as creating interprofessional and community-based opportunities. Discussion: This evaluation offers in-depth student perspectives of our climate and health curriculum. Opportunities exist to synergize climate and health education with broader transformations in medicine towards health promotion and sustainable, climate-ready healthcare. From the input of focus groups, the authors derive a framework for strengthening and extending curricular content.